VALIDATION OF AAS ANALYSIS PROTOCOLS FOR TUNA FISH HOMOGENATE: IAEA-436 - Khalid, N.; Rahman, S.; Zaidi, J. H. (The Nucleus, 2020)
Tuna fish flesh homogenate, IAEA-436, a certified reference material received from IAEA under the Analytical Quality Control Services intercomparison programme for trace metal determination, was analyzed for Cu, Fe, K, Mg, Mn and Zn by using atomic absorption spectrophotometric (AAS) technique employing the optimized instrumental parameters. The reliability of the methodology adopted was checked by analyzing IAEA-CRM (Copepod Homogenate MA-A-1) under identical conditions and comparing the results obtained with the certified values which are in quite good agreement with each other. High precision was observed for Fe, K, Mg and Zn, whereas Cu and Mn showed relatively poor precision in their determination.